Managing Your Tropical Fruit Grove Under Changing Water Table Levels - Carlos F. Balerdi; Jonathan H. Crane; Bruce Schaffer (EDIS)
This fact sheet has been prepared by IFAS faculty working with tropical fruit crops in an effort to assist growers manage their groves under conditions of flooding, high water tables, or drought. Although weather events cannot be controlled, becoming familiar with the effects of a high water table, flooding, or drought on tropical fruit crops may assist growers in managing their fruit trees so they survive these events with minimal or no damage. However, this process will be impacted by ground water levels, which are managed in south Florida, and thus are dependent on regional water management decisions. This document is Fact Sheet HS957, one of a series of Horticultural Sciences Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published November 2003.